Design and Psychometric Evaluation of the Place Attachment Scale for Older Adults in Iran - Zahra Aliakbarzadeh Arani; Nasibeh Zanjari; Ahmad Delbari; Mahshid Foroughan; Gholamreza Ghaedamini Harouni (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives Due to the importance of place attachment in older adults, it seems necessary to identify their perception of this concept and its dimensions. The present study aims to design and assess the psychometric properties of a place attachment scale for older adults in Iran. Methods & Materials The is a sequential exploratory mixed method study that was conducted in 2018-2019 in two quantitative and qualitative phases. Participants were 414 community-dwelling older adults with a mean age of 70.43±8.84 years in Aran & Bidgol city, Iran who were selected by cluster sampling according to the inclusion criteria. By literature review and interview, the items were formulated. The face and validity content validity of the initial draft was assessed by a panel of experts and older adults. The construct validity was determined by exploratory and confirmatory factor analyses. The internal consistency and test-retest reliability were also determined. SPSS software, version 24 and AMOS version 24 applications were used for statistical analysis. Results In examining content validity, most of items had content validity ratio >0.7, content validity index >0.79, and kappa coefficient >0.74. In examining construct validity using exploratory factor analysis, three factors of emotional bond, physical bond, and dependence were extracted for the subscale of attachment to home and three factors of emotional bond, social bond, and physical bond were extracted for the subscale of attachment to neighborhood, which explained 61.75% and 50.06% of the total variance, respectively. The measurement models of attachment to home (GFI=0.877, CFI=0.916, RMSEA=0.080) and neighborhood (GFI=0.809, CFI=0.860, RMSEA=0.077) had acceptable fit to the data. Moreover, the scale had acceptable internal consistency (α= 0.9) and test-retest reliability (ICC= 0.8). Conclusion The designed 42-item place attachment scale with two domains of attachment to home and neighborhood for the community-dwelling older adults in Iran has acceptable validity and reliability. This tool can be used in further studies and by policymaking in Iran.